Prediction of the remaining useful life for plate heat exchanger at Hai Thach - Moc Tinh fields - Tran, Ngoc Trung; Nguyen, Thanh Trung; Nguyen, Duy Minh; Dao, Quang Khoa; Tran, Vu Tung; Tran, Duc Thang (Petrovietnam Journal, 2024)
Predictive maintenance is an advanced and widely adopted approach in the industry that helps maximize the equipment uptime by estimating its remaining useful life (RUL) and predicting any potential failure point. The authors have made a short-term prediction of the seawater flow pressure difference at a plate heat exchanger using a long short-term memory (LSTM) network, and thereby predicted the RUL using a nonlinear regression model. The proposed model achieved high accuracy by continuously detecting checkpoints and predicting RUL values every 24 hours. Checkpoints are identified through detecting differential pressure anomalies at the plate heat exchanger during operation. Thereby, it helps update the RUL value promptly upon any unforeseen deviation during equipment operation.